2013
DOI: 10.1590/s0074-02762013005000005
|View full text |Cite
|
Sign up to set email alerts
|

Schistogram changes after administration of antischistosomal drugs in mice at the early phase of Schistosoma mansoni infection

Abstract: Mice infected with Schistosoma mansoni were treated with oxamniquine, praziquantel, artesunate at the pre-patent phase, aiming at observing schistogram alterations. Half of the animals were perfused five days post-treatment for counting and classification of immature worms, based on pre-established morphological criteria (schistogram); the remaining animals were evaluated 42 or 100 days after infection and perfusion of the portal-system was performed for collection and counting of adult worms and oogram. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…PZQ treatment did not cause any significant reduction of schistosomula count when compared to positive control group. This agreed with Vimieiro et al (2013) who found that PZQ administered at the day 14 p.i. caused only little reduction of immature S. mansoni worms.…”
Section: Introductionsupporting
confidence: 92%
“…PZQ treatment did not cause any significant reduction of schistosomula count when compared to positive control group. This agreed with Vimieiro et al (2013) who found that PZQ administered at the day 14 p.i. caused only little reduction of immature S. mansoni worms.…”
Section: Introductionsupporting
confidence: 92%
“…These results are supported by a number of studies on other anti-schistosomal therapeutic agents. When juvenile S. mansoni worms are treated early, they fail to produce eggs due to the inhibitory effect of anti-schistosomals on their sexual maturation, causing atrophy of their testes and ovaries, hence confirming the advantage of early treatment (Hamza et al , 2012; Vimieiro et al, 2013). In context, several studies have demonstrated that immature worms are less susceptible to PZQ (Botros et al , 2005; Grandière-Pérez et al ., 2006; Vimieiro et al , 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Vimieiro et al (2013) described efficient treatment of schistosomiasis during the initial phase of infection as an important challenge. An ideal treatment would inhibit egg production and consequently granuloma formation, which is the main cause of the pathology of this disease (Coelho et al , 2009).…”
Section: Discussionmentioning
confidence: 99%